The distributive Effects of Education: An Unconditional Quantile Regression Approach - Javier Alejo; María Florencia Gabrielli; Walter Sosa Escudero (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2011)
We use recent unconditional quantile regression methods (UQR) to study the distributive effects of education in Argentina. Standard methods usually focus on mean effects, or explore distributive effects by either making stringent modeling assumptions, and/or through counterfactual decompositions that require several temporal observations. An empirical case shows the exibility and usefulness of UQR methods. Our application for the case of Argentina shows that education contributed positively to increased inequality in Argentina, mostly due to the effect of strongly heterogeneous effects of education on earnings. – unconditional quantile regression ; income inequality ; education ; Argentina – – En este trabajo utilizamos los más recientes métodos de regresión no condicionada por cuantiles (RNCQ) para estudiar los efectos distributivos de la educación en Argentina. Los métodos estándar se centran, por lo general, en efectos promedio o estudian los efectos distributivos ya sea haciendo uso de suposiciones estrictas al modelar y/o a través de descomposiciones contrafácticas que requieren varias observaciones temporales. La aplicación empírica en este trabajo muestra la flexibilidad y utilidad de los métodos de RNCQ. Nuestra aplicación para el caso de Argentina sugiere que la educación ha contribuido positivamente al aumento de la desigualdad, debido principalmente a efectos fuertemente heterogéneos de la educación sobre los ingresos.
Keywords: C21; I24; I31; D3; 330; unconditional quantile regression; income inequality; education; Argentina; Bildungsertrag; Einkommensverteilung; Argentinien